Role of macrophages in peritoneal dialysis-associated peritoneal fibrosis - Chenling Chu; Ying Huang; Luxi Cao; Shuiyu Ji; Bin Zhu; Quanquan Shen (Renal Failure)
Peritoneal dialysis (PD) can be used as renal replacement therapy when chronic kidney disease (CKD) progresses to end-stage renal disease. However, peritoneal fibrosis (PF) is a major cause of PD failure. Studies have demonstrated that PD fluid contains a significantly larger numbers of macrophages compared with the healthy individuals. During PD, macrophages can secrete cytokines to keep peritoneal tissue in sustained low-grade inflammation, and participate in the regulation of fibrosis-related signaling pathways, such as NF-κB, TGF-β/Smad, IL4/STAT6, and PI3K/AKT. A series of basic pathological changes occurs in peritoneal tissues, including epithelial mesenchymal transformation, overgeneration of neovasculature, and abnormal deposition of extracellular matrix. This review focuses on the role of macrophages in promoting PF during PD, summarizes the targets of macrophage-related inhibition of fibrosis, and provides new ideas for clinical research on delaying PF, maintaining the function and integrity of peritoneum, prolonging duration of PD as a renal replacement modality, and achieving longer survival in CKD patients.